PERLINDUNGAN HUKUM KREDITUR TERHADAP DEBITUR YANG MENGGUNAKAN PRINSIP CROSS DEFAULT DAN COLLATERAL DALAM PERJANJIAN KREDIT: Legal Protection of Creditors against Debtors who use Cross Default and Collateral Principles in Credit Agreements - Safira, Excha Restya (Fakultas Hukum, Universitas Trisakti, 2024)
This scientific research aims to outline the legal protection that creditors get to debtors who use the principles of cross default and cross collateral in credit agreements. In this scientific research, the method used is normative law that uses legislation as a source of data. The technique of collecting legal documents uses literature study techniques. The results of this scientific research show that the Cross Default and Cross Collateral principles by using the debtor's guarantee object can create one or more different credit facilities that use the same collateral, while the creditor remains protected because the existence of the Cross Default and Cross Collateral principles aims to anticipate if in the future there is a defaulting party and the creditor can still demand responsibility for the negligence.